Manufacturing method of lithium niobate and lithium tantalate black reduced wafer

By using chemical glue and toner reducing agent printing process on lithium niobate and lithium tantalate wafers, the problems of insecurity and high cost in the prior art are solved, and low pyroelectricity and high yield are achieved The large-scale production of lithium niobate and lithium tantalate blackened wafers meets the production needs of RF devices.

CN119162672APending Publication Date: 2024-12-20GUANGZHOU JINGHONG NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411158843.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing lithium niobate and lithium tantalate blackening processes are insecure, high cost and inability to meet the demand for low pyroelectricity and high yield of RF devices, especially in miniaturization and mass production processes.

Method used

After using wire cutting and chamfering treatment, use special chemical glue and toner reducing agent to blacken the reducing agent at a temperature of 300~500℃, apply the reducing agent evenly through the printing process, and perform insulation treatment in the crucible to achieve Blackening of the chip.

Benefits of technology

The uniformity and mass production of lithium niobate and lithium tantalate blackened wafers are achieved, reducing production risks, saving costs, and improving the production yield of radio frequency devices, meeting the requirements of low static charge.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a manufacturing method of a lithium niobate and lithium tantalate black reduced wafer, which comprises the following steps of: cutting lithium niobate [LN] and lithium tantalate [LT] crystals into original wafers with required thickness by adopting a wire cutting machine, chamfering the edges of the wafers into C-shaped edges by using a chamfering machine, and then putting the C-shaped edges into corrosive liquid to corrode for 8-10 hours so as to reduce the internal stress of the wafers. According to the reduction mechanism, + 5 valence niobium or tantalum is reduced to + 4 or + 3 valence, and the color of the wafer is changed; according to the invention, the reduction uniformity of the lithium niobate [LN] and lithium tantalate [LT] black wafers is realized, the mass production of the lithium niobate [LN] and lithium tantalate [LT] reduced black wafers with low pyroelectric effect is realized, and the requirement on low electrostatic charge in the radio frequency device semiconductor plane process production is met, so that the production yield of radio frequency device chips is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wafers, and in particular to a method for manufacturing a lithium niobate or lithium tantalate black reduced wafer. Background Art

[0002] Conventional lithium niobate [LN] and lithium tantalate [LT] wafers are nearly white and translucent. During the manufacturing process of RF devices, a large amount of static electricity will accumulate on the surface of the wafer. With the further miniaturization of RF devices and the further increase in the frequency of RF devices, the wafer is required to have lower pyroelectricity to reduce the generation of static charge, thereby improving the yield of RF devices. In order to meet the production needs of miniaturization, high yield, and large quantities of RF devices, the wafer needs to be reduced and blackened to reduce the generation and accumulation of static charge. The reduction and blackening of lithium niobate [LN] and lithium tantalate [LT] effectively solves the problem of static electricity accumulation on the surface of ordinary white wafers, and obtains wafers with low pyroelectric effect, which can better meet the production requirements of RF device semiconductor planar processes than conventional white wafers.

[0003] In order to meet the needs of the market and solve the production defects of other blackening processes such as unsafety and high cost, the present invention further improves and processes them. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a method for preparing lithium niobate and lithium tantalate black reduction wafers to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution: The present invention provides a method for manufacturing a black reduction wafer of lithium niobate or lithium tantalate, comprising the following steps: Step 1: Use a wire cutting machine to cut lithium niobate [LN] and lithium tantalate [LT] crystals into original wafers of the required thickness, then use a chamfering machine to chamfer the edges of the wafers into C-shaped edges, and then place them in an etching solution for 8 to 10 hours to reduce the internal stress of the wafers; Step 2: Prepare a special reducing agent; Step 3: Prepare glue: Mix chemical pulp and water in a mass ratio of 1:10; Step 4: Preparation of the colloidal reducing agent for printing: Mix the mixed powdered reducing agent and glue in a mass ratio of 1:1 to form a colloidal reducing agent; Step 5: Screen for painting: Use 300 mesh screen for printing; Step 6: Brushing: Clean the original white lithium niobate [LN] or lithium tantalate [LT] film, cover the surface of the wafer with a printing screen, evenly apply the colloidal reducing agent on the screen, use a printing roller to evenly apply a layer of reducing agent on the surface of the wafer, and then place it in the air to dry naturally; use the same method to print the second side; Step 7: Loading the furnace: Place naturally air-dried lithium niobate [LN] or lithium tantalate [LT] wafers in a stack of 25 or 50 wafers into a crucible, fill the crucible gap with carbon powder to cover the wafers, then place them into the furnace, close the furnace door and heat up. The temperature of lithium niobate [LN] wafers is raised to 300~400℃, and the temperature of lithium tantalate [LT] wafers is raised to 400~500℃. Keep warm for 2 hours, then naturally cool to room temperature. Take out the wafers and scrape off the reducing agent on the surface. The wafers will then appear black or brown.

[0006] Preferably, the reducing agent is prepared by uniformly mixing iron powder, basic carbonate and carbon powder in a mass ratio of 1:1:8.

[0007] Preferably, the carbon powder is also subjected to ultrasonic treatment with a modifying liquid; The preparation method of the modified liquid is as follows: 2-5 parts of sodium dodecylbenzene sulfonate solution are added to 4-7 parts of chitosan solution, and then 1-3 parts of yttrium oxide and 2-4 parts of silane coupling agent KH560 are added and stirred to obtain the modified liquid.

[0008] Preferably, the mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%; the mass fraction of the chitosan solution is 4-7%.

[0009] Preferably, the ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.

[0010] Preferably, the ultrasonic power is 375W and the ultrasonic time is 25min.

[0011] Preferably, the chemical pulp is a polyurethane adhesive matrix, which is the existing raw material in document CN113897166B.

[0012] Blackening reduction mechanism: Niobium or tantalum oxide or +5 valence is white, and the color will change only when the valence is reduced. The present invention adopts special chemical glue and reducing agents such as carbon powder according to the characteristics of niobium or tantalum, and solves the reduction problem in the temperature range of about 300~500℃.

[0013] Compared with the prior art, the present invention has the following beneficial effects: The present invention urgently needs to develop a new type of processing technology that can be processed in large quantities and can ensure uniform blackening reduction and controllable costs, so as to realize large-scale production of lithium niobate [LN] and lithium tantalate [LT] reduction blackening wafers; no dangerous gases such as hydrogen are introduced during the reduction process, which reduces the production risk and saves costs; the reducing agent uses iron powder, basic carbonate, and carbon powder, which are easy to purchase on the market, and the reactants generated in the process are harmless and easy to recycle; the reducing agent is applied by a printing process, which is efficient and controllable in precision and is suitable for large-scale production; the reduction temperature is lower than 500° C., which is lower than the temperature of other production processes and saves energy.

[0014] The reduction mechanism of the present invention is to reduce the +5 valence of niobium or tantalum to +4 or +3 valence, thereby realizing the change of the color of the chip; the present invention realizes the reduction uniformity of lithium niobate [LN] and lithium tantalate [LT] black chips, realizes the mass production of lithium niobate [LN] and lithium tantalate [LT] reduced black chips with low pyroelectric effect, meets the requirement for low static charge in the planar process production of radio frequency device semiconductors, and thus greatly improves the production yield of radio frequency device chips. DETAILED DESCRIPTION

[0015] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0016] The method for manufacturing a lithium niobate or lithium tantalate black reduction wafer of the present embodiment comprises the following steps: Step 1: Use a wire cutting machine to cut lithium niobate [LN] and lithium tantalate [LT] crystals into original wafers of the required thickness, then use a chamfering machine to chamfer the edges of the wafers into C-shaped edges, and then place them in an etching solution for 8 to 10 hours to reduce the internal stress of the wafers; Step 2: Prepare a special reducing agent; Step 3: Prepare glue: Mix chemical pulp and water in a mass ratio of 1:10; Step 4: Preparation of the colloidal reducing agent for printing: Mix the mixed powdered reducing agent and glue in a mass ratio of 1:1 to form a colloidal reducing agent; Step 5: Screen for painting: Use 300 mesh screen for printing; Step 6: Brushing: Clean the original white lithium niobate [LN] or lithium tantalate [LT] film, cover the surface of the wafer with a printing screen, evenly apply the colloidal reducing agent on the screen, use a printing roller to evenly apply a layer of reducing agent on the surface of the wafer, and then place it in the air to dry naturally; use the same method to print the second side; Step 7: Loading the furnace: Place naturally air-dried lithium niobate [LN] or lithium tantalate [LT] wafers in a stack of 25 or 50 wafers into a crucible, fill the crucible gap with carbon powder to cover the wafers, then place them into the furnace, close the furnace door and heat up. The temperature of lithium niobate [LN] wafers is raised to 300~400℃, and the temperature of lithium tantalate [LT] wafers is raised to 400~500℃. Keep warm for 2 hours, then naturally cool to room temperature. Take out the wafers and scrape off the reducing agent on the surface. The wafers will then appear black or brown.

[0017] Preferably, the reducing agent is prepared by uniformly mixing iron powder, basic carbonate and carbon powder in a mass ratio of 1:1:8.

[0018] The carbon powder of this embodiment is also subjected to ultrasonic treatment of the modification liquid; The preparation method of the modified liquid is as follows: 2-5 parts of sodium dodecylbenzene sulfonate solution are added to 4-7 parts of chitosan solution, and then 1-3 parts of yttrium oxide and 2-4 parts of silane coupling agent KH560 are added and stirred to obtain the modified liquid.

[0019] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 2-5%; the mass fraction of the chitosan solution is 4-7%.

[0020] The ultrasonic power of the ultrasonic treatment in this embodiment is 350-400W, and the ultrasonic time is 20-30min.

[0021] The ultrasonic power of this embodiment is 375W, and the ultrasonic time is 25min.

[0022] The chemical pulp of this embodiment is a polyurethane adhesive matrix, which is the existing raw material in the document CN113897166B.

[0023] Example 1. The method for manufacturing a lithium niobate or lithium tantalate black reduction wafer of the present embodiment comprises the following steps: Step 1: Use a wire cutting machine to cut lithium niobate [LN] and lithium tantalate [LT] crystals into original wafers of required thickness, then use a chamfering machine to chamfer the edges of the wafers into C-shaped edges, and then place them in an etching solution for 8 hours to reduce the internal stress of the wafers; Step 2: Prepare a special reducing agent; Step 3: Prepare glue: Mix chemical pulp and water in a mass ratio of 1:10; Step 4: Preparation of the colloidal reducing agent for printing: Mix the mixed powdered reducing agent and glue in a mass ratio of 1:1 to form a colloidal reducing agent; Step 5: Screen for painting: Use 300 mesh screen for printing; Step 6: Brushing: Clean the original white lithium niobate [LN] or lithium tantalate [LT] film, cover the surface of the wafer with a printing screen, evenly apply the colloidal reducing agent on the screen, use a printing roller to evenly apply a layer of reducing agent on the surface of the wafer, and then place it in the air to dry naturally; use the same method to print the second side; Step 7: Loading the furnace: Place naturally air-dried lithium niobate [LN] or lithium tantalate [LT] wafers in a stack of 25 or 50 wafers into a crucible, fill the crucible gap with carbon powder to cover the wafers, then place them into the furnace, close the furnace door and heat up. The temperature of lithium niobate [LN] wafers is raised to 300°C, and the temperature of lithium tantalate [LT] wafers is raised to 400°C. Keep warm for 2 hours, then naturally cool to room temperature. Take out the wafers and scrape off the reducing agent on the surface. The wafers will then appear black or brown.

[0024] Preferably, the reducing agent is prepared by uniformly mixing iron powder, basic carbonate and carbon powder in a mass ratio of 1:1:8.

[0025] The carbon powder of this embodiment is also subjected to ultrasonic treatment of the modification liquid; The preparation method of the modified liquid is as follows: 2 parts of sodium dodecylbenzene sulfonate solution are added to 4-7 parts of chitosan solution, and then 1 part of yttrium oxide and 2 parts of silane coupling agent KH560 are added and stirred to obtain the modified liquid.

[0026] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 2%; the mass fraction of the chitosan solution is 4%.

[0027] The ultrasonic power of the ultrasonic treatment in this embodiment is 350W, and the ultrasonic time is 20min.

[0028] The chemical pulp of this embodiment is a polyurethane adhesive matrix, which is the existing raw material in the document CN113897166B.

[0029] Example 2. The method for manufacturing a lithium niobate or lithium tantalate black reduction wafer of the present embodiment comprises the following steps: Step 1: Use a wire cutting machine to cut lithium niobate [LN] and lithium tantalate [LT] crystals into original wafers of required thickness, then use a chamfering machine to chamfer the edges of the wafers into C-shaped edges, and then place them in an etching solution for 10 hours to reduce the internal stress of the wafers; Step 2: Prepare a special reducing agent; Step 3: Prepare glue: Mix chemical pulp and water in a mass ratio of 1:10; Step 4: Preparation of the colloidal reducing agent for printing: Mix the mixed powdered reducing agent and glue in a mass ratio of 1:1 to form a colloidal reducing agent; Step 5: Screen for painting: Use 300 mesh screen for printing; Step 6: Brushing: Clean the original white lithium niobate [LN] or lithium tantalate [LT] film, cover the surface of the wafer with a printing screen, evenly apply the colloidal reducing agent on the screen, use a printing roller to evenly apply a layer of reducing agent on the surface of the wafer, and then place it in the air to dry naturally; use the same method to print the second side; Step 7: Loading the furnace: Place naturally air-dried lithium niobate [LN] or lithium tantalate [LT] wafers in a stack of 25 or 50 wafers into a crucible, fill the crucible gap with carbon powder to cover the wafers, then place them into the furnace, close the furnace door and heat up. The temperature of lithium niobate [LN] wafers is raised to 400°C, and the temperature of lithium tantalate [LT] wafers is raised to 500°C. Keep warm for 2 hours, then cool naturally to room temperature. Take out the wafers and scrape off the reducing agent on the surface. The wafers will then appear black or brown.

[0030] Preferably, the reducing agent is prepared by uniformly mixing iron powder, basic carbonate and carbon powder in a mass ratio of 1:1:8.

[0031] The carbon powder of this embodiment is also subjected to ultrasonic treatment of the modification liquid; The preparation method of the modified liquid is as follows: 5 parts of sodium dodecylbenzene sulfonate solution are added to 7 parts of chitosan solution, and then 3 parts of yttrium oxide and 4 parts of silane coupling agent KH560 are added and stirred to obtain the modified liquid.

[0032] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 5%; the mass fraction of the chitosan solution is 7%.

[0033] The ultrasonic power of the ultrasonic treatment in this embodiment is 400 W, and the ultrasonic time is 30 min.

[0034] The chemical pulp of this embodiment is a polyurethane adhesive matrix, which is the existing raw material in the document CN113897166B.

[0035] Example 3. The method for manufacturing a lithium niobate or lithium tantalate black reduction wafer of the present embodiment comprises the following steps: Step 1: Use a wire cutting machine to cut lithium niobate [LN] and lithium tantalate [LT] crystals into original wafers of the required thickness, then use a chamfering machine to chamfer the edges of the wafers into C-shaped edges, and then place them in an etching solution for 8 to 10 hours to reduce the internal stress of the wafers; Step 2: Prepare a special reducing agent; Step 3: Prepare glue: Mix chemical pulp and water in a mass ratio of 1:10; Step 4: Preparation of the colloidal reducing agent for printing: Mix the mixed powdered reducing agent and glue in a mass ratio of 1:1 to form a colloidal reducing agent; Step 5: Screen for painting: Use 300 mesh screen for printing; Step 6: Brushing: Clean the original white lithium niobate [LN] or lithium tantalate [LT] film, cover the surface of the wafer with a printing screen, evenly apply the colloidal reducing agent on the screen, use a printing roller to evenly apply a layer of reducing agent on the surface of the wafer, and then place it in the air to dry naturally; use the same method to print the second side; Step 7: Loading the furnace: Place naturally air-dried lithium niobate [LN] or lithium tantalate [LT] wafers in a stack of 25 or 50 wafers into a crucible, fill the crucible gap with carbon powder to cover the wafers, then place them into the furnace, close the furnace door and heat up. The temperature of lithium niobate [LN] wafers is raised to 350°C, and the temperature of lithium tantalate [LT] wafers is raised to 450°C. Keep warm for 2 hours, then naturally cool to room temperature. Take out the wafers and scrape off the reducing agent on the surface. The wafers will then appear black or brown.

[0036] Preferably, the reducing agent is prepared by uniformly mixing iron powder, basic carbonate and carbon powder in a mass ratio of 1:1:8.

[0037] The carbon powder of this embodiment is also subjected to ultrasonic treatment of the modification liquid; The preparation method of the modified liquid is as follows: 3.5 parts of sodium dodecylbenzene sulfonate solution are added to 5.5 parts of chitosan solution, and then 2 parts of yttrium oxide and 3 parts of silane coupling agent KH560 are added and stirred to obtain the modified liquid.

[0038] The mass fraction of the sodium dodecylbenzene sulfonate solution in this embodiment is 3.5%; the mass fraction of the chitosan solution is 5.5%.

[0039] The ultrasonic power of this embodiment is 375W, and the ultrasonic time is 25min.

[0040] The chemical pulp of this embodiment is a polyurethane adhesive matrix, which is the existing raw material in the document CN113897166B.

[0041] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0042] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A method for producing a black reduction wafer of lithium niobate or lithium tantalate, It is characterized in that The following steps are involved: Step 1: Use a wire cutting machine to cut lithium niobate [LN] and lithium tantalate [LT] crystals into original wafers of the required thickness, then use a chamfering machine to chamfer the edges of the wafers into C-shaped edges, and then place them in an etching solution for 8 to 10 hours to reduce the internal stress of the wafers; Step 2: Prepare a special reducing agent; Step 3: Prepare glue: Mix chemical pulp and water in a mass ratio of 1:10; Step 4: Preparation of the colloidal reducing agent for printing: Mix the mixed powdered reducing agent and glue in a mass ratio of 1:1 to form a colloidal reducing agent; Step 5: Screen for painting: Use 300 mesh screen for printing; Step 6: Brushing: Clean the original white lithium niobate [LN] or lithium tantalate [LT] film, cover the surface of the wafer with a printing screen, evenly apply the colloidal reducing agent on the screen, use a printing roller to evenly apply a layer of reducing agent on the surface of the wafer, and then place it in the air to dry naturally; use the same method to print the second side; Step 7: Loading the furnace: Place naturally air-dried lithium niobate [LN] or lithium tantalate [LT] wafers in a stack of 25 or 50 wafers into a crucible, fill the crucible gap with carbon powder to cover the wafers, then place them into the furnace, close the furnace door and heat up. The temperature of lithium niobate [LN] wafers is raised to 300~400℃, and the temperature of lithium tantalate [LT] wafers is raised to 400~500℃. Keep warm for 2 hours, then naturally cool to room temperature. Take out the wafers and scrape off the reducing agent on the surface. The wafers will then appear black or brown.

2. A method for producing a lithium niobate or lithium tantalate black reduction wafer according to claim 1, It is characterized in that The preparation method of the reducing agent is as follows: iron powder, basic carbonate and carbon powder are uniformly mixed in a mass ratio of 1:1:

8.

3. The method for manufacturing a lithium niobate or lithium tantalate black reduction wafer according to claim 1, It is characterized in that The carbon powder is also subjected to ultrasonic treatment with a modification liquid; The preparation method of the modified liquid is as follows: 2-5 parts of sodium dodecylbenzene sulfonate solution are added to 4-7 parts of chitosan solution, and then 1-3 parts of yttrium oxide and 2-4 parts of silane coupling agent KH560 are added and stirred to obtain the modified liquid.

4. The method for manufacturing a lithium niobate or lithium tantalate black reduction wafer according to claim 3, It is characterized in that The mass fraction of the sodium dodecylbenzene sulfonate solution is 2-5%; the mass fraction of the chitosan solution is 4-7%.

5. The method for manufacturing a lithium niobate or lithium tantalate black reduction wafer according to claim 3, It is characterized in that The ultrasonic power of the ultrasonic treatment is 350-400W, and the ultrasonic time is 20-30min.

6. The method for manufacturing a lithium niobate or lithium tantalate black reduction wafer according to claim 5, It is characterized in that The ultrasonic power is 375W, and the ultrasonic time is 25min.

7. The method for manufacturing a lithium niobate or lithium tantalate black reduction wafer according to claim 1, It is characterized in that The chemical pulp is a polyurethane adhesive matrix, which is the existing raw material in document CN113897166B.